(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Fast food is very popular among adolescents but its consumption has been associated with negative impact on health. This study was conducted to assess the fast food consumption pattern and eating behavior of adolescent girls and also the amount of money they spent on consumption of fast food from hostel canteen as well as outside places. The change in lifestyle has led to change in the consumption pattern in the recent years which has created a high demand for food products in processed and preserved form. Many of the adolescents exhibit peculiar food habits. Peer influence is one of the main reasons for faulty eating habits among the adolescents. Generally this becomes a habit resulting in a host of malnutrition related problem. Adolescents are at risk of many non communicable disease like obesity, diabetes, hypertension etc due to irregular eating habits. These eating habits of adolescents may even go into their adulthood. The study on fast food and snacks usage among adolescent girls was conducted among 50 adolescent girls in Maharshi Dayanand University, Rohtak in Haryana.